Investigation of the Influence of Formulation Method on Technological Parameters of Gramicidin S and β-cyclodextrin Inclusion Complexes - A. A. Drannikov; I. S. Vatlin; M. E. Trusova; A. Di Martino; S. V. Krivoshchekov; A. M. Guriev; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. Gramicidin S is a peptide antibiotic that has been widely used for more than 70 years. Gramicidin S is available in the form of tablets with a low dosage, which leads to possible deviations in the "Uniformity of dosage" parameter during manufacturing. Another limitation is the presence of lactose and sucrose in the formulation, which limits the drug application by patients demonstrating intolerance. As an alternative, we propose inclusion complexes of gramicidin S with β-cyclodextrin.Aim. The work aims to describe the influence of the methodology to prepare the inclusion complex on the characteristics and properties of the final product.Materials and methods. The gramicidin S – β-cyclodextrin inclusion complex has been prepared by dry mixing, paste complexation, co-precipitation and fluid-bed complexation. The complex formation has been confirmed by 1H NMR spectroscopy, differential scanning calorimetry and thermogravimetry while the morphology and size by scanning electron microscopy for the solid and dynamic light scattering for the solution. The flowability, slope angle, bulk density of the obtained powders were estimated using the methods described in Russian Pharmacopoeia of the XIV edition.Results and discussion. In the present work, we prepared a set of gramicidin S and β-cyclodextrin inclusion complexes by various approaches. The thermal analysis demonstrated a significant change in the peak referring to phase transition of the substances, indicating the interaction between the components. The 1H NMR spectroscopy reveals that the L-ornithine amino group is the part of gramicidin S involved in the complexation. Evaluating the technological properties of gramicidin S and β-cyclodextrin inclusion complexes significant variability, which is associated with the particle morphology. Complexes obtained using co-precipitation and fluid-bed complexation methods are more suitable for producing gramicidin S tablet production by direct compression technology.Conclusion. Herein, we demonstrate that the formation of the gramicidin S and β-cyclodextrin inclusion complex occurs through the L-ornithine amino group in the gramicidin S. In addition, depending on the method significant differences in the particle size and shape have been observed. The obtained results could provide valuable information for the development of new gramicidin S buccal formulations, which are more consistent in the "Uniformity of dosage" and allow to avoid the use of lactose and sucrose as excipients.